An Insight into Genetic Diversity and Risk Factors of Ovine and Caprine Babesiosis in Erbil Governorate, Northern of Iraq - Aziz, Khlaid (The Iraqi Journal of Veterinary Medicine, 2025)
Ovine and caprine babesiosis is a significant tick-borne disease affecting small ruminants, causing economic losses and health challenges in endemic regions such as northern Iraq. This study aimed to determine the prevalence, molecular characteristics, and associated risk factors of Babesia spp. infections in small ruminants in Erbil Province, Iraq. A total of 235 animals (125 sheep and 110 goats) were clinically examined and sampled between October 2024 and March 2025. Blood smears were screened microscopically, and DNA was extracted from the blood sample collected for molecular detection. PCR targeting the 18S rRNA gene of Babesia spp., B. ovis, and B. motasi was carried out using the extracted DNA from the blood samples. Microscopic examination results revealed infection rates to be 16.8% in sheep and 8.2% in goats, while PCR-based detection showed notably higher prevalence, 28.8% and 12.7%, respectively. Sequencing and phylogenetic analysis of B. ovis isolates confirmed strong genetic similarity with regional strains from Turkey, Iran, and Iraq. Additionally, the presence of B. ovis sequences clustering with those from non-ruminant hosts (e.g., rabbits and horses) was observed. Notably, Babesia motasi was not detected in any of the examined samples. Risk factor analysis demonstrated significant associations between infection and tick infestation, lack of acaricide use, and prior exposure to ticks. Specifically, tick-infested animals exhibited markedly higher infection rates, with odds ratios of 9.93 for sheep and 4.16 for goats. However, no statistically significant differences were observed concerning sex, age, or grazing system. These findings underscore the continued threat of Babesia infections among small ruminants in northern Iraq and highlight the need for improved tick control strategies to mitigate disease transmission‎‎‎.